Bibliometric Analysis of HHO Gas Production by Electrolysis from 2013 to 2023 - Purwono Purwono; H Hadiyanto; Mochamad Arief Budihardjo; Annisa Sila Puspita (Universitas Diponegoro, 2023)
HHO gas is one promising alternative as an alternative for fossil fuels, nevertheless, several challenges need to be overcome in order for HHO gas to become a viable option for global use. This paper presentsbibliometric analysis, HHO gases production methods, and challenges of using HHO gas. The primary objective of this review paper is to provide views, assessments, and evaluations of the published literature on HHO gas, both the production and use challenges of HHO gas. This review article uses several software programs including origin for graph visualization, Microsoft excel for processing data, and VOSviewer for analyzing bibliographic mappings. HHO production can be done by adding KOH electrolyte solution. Factors that affect the production of HHO gas include electrolyte properties, electrolyte concentration, and distance between electrodes. An increase in the concentration of the electrolysis solution leads to an increase in the production of HHO gas. The production of HHO gas can also be done with the addition of Na2CO3 or K2CO3 which can produce high H2 gas. The pre-combustion mercury removal technique using coal electrolysis produces hydrogen byproducts with 50% less energy than water electrolysis. A single Pt circuit at TiO2 support (Pt1/def-TiO2) forms a highly efficient photocatalyst for hydrogen production. The main challenges of HHO gas in terms of production, storage, distribution, safety, cost of HHO gas production.